Which safe zone is safe in total hip arthroplasty?: The effect of bony impingement - Weber, Markus; Kunow, Frederik von; Innmann, Moritz Maximilian; Meyer, Matthias; Thieme, Max; Jerabek, Seth; Renkawitz, Tobias (Journal of Personalized Medicine, 2022)
“Safe zones” for cup position are currently being investigated in total hip arthroplasty (THA). This study aimed to evaluate the impact of bony impingement on the safe zone and provide recommendations for cup position in THA. CT scans were performed on 123 patients who underwent a cementless THA. Using the implant data and bone morphology from the CT scans, an impingement detection algorithm simulating range of motion (ROM) determined the presence of prosthetic and/or bony impingement. An impingement-free zone of motion was determined for each patient. These zones were then compared across all patients to establish an optimized impingement-free “safe zone”. Bony impingement reduced the impingement-free zone of motion in 49.6% (61/123) of patients. A mean reduction of 23.4% in safe zone size was observed in relation to periprosthetic impingement. The superposition of the safe zones showed the highest probability of impingement-free ROM with cup position angles within 40-50° of inclination and 20-30° of anteversion in relation to the applied cup and stem design of this study. Virtual ROM simulations identified bony impingement at the anterosuperior acetabular rim for internal rotation at 90° of flexion and at the posteroinferior rim for adduction as the main reasons for bony impingement.